System Research and Optimization of Coffee-Based Agricultural Land as a Sustainable Forest Management Alternative - Budiyono Budiyono; Abdul Rauf; Satia Negara Lubis; Sabrina Sabrina (Green Publisher, 2025)
Biodiversity decline has significant implications for environmental sustainability, necessitating an integrated approach to environmental planning and management. Environmental degradation is closely linked to socio-economic conditions, particularly poverty and economic growth. In response to this issue, this research aims to analyze the development of coffee-based agroforestry systems in forest areas to optimize land use in Humbang Hasundutan Regency, North Sumatra, Indonesia. The research employs a quantitative approach, with coffee farmers practicing agroforestry in forest areas as the research population and sample. The findings indicate that a more suitable and sustainable agroforestry system for this region is the agrosilvopastoral model, which integrates trees, agricultural crops, and fodder grasses. This system is particularly effective in steep and very steep terrains with shallow and loose soil. Additionally, in basin areas near springs and rivers, agroaquaforestry or agroaquasilvicultural systems are recommended, incorporating agricultural crops, trees, fish ponds, and fodder grass to maintain environmental stability. The implications of this research suggest that implementing these agroforestry models can enhance land productivity, support farmers' economic sustainability, and contribute to environmental conservation in forest areas.